Climate Variability and Its Impact on Acute Respiratory Infections: A Case Study - Suhito, Hanif Pandu; Cahyati, Widya Hary; Ningrum, Dina Nur Anggraini; Sholikun, Sholikun (Universitas Negeri Semarang, 2025)
This study aims to analyze the relationship between climate variability and acute respiratory infection (ARI) cases in Semarang City over the period 2015-2023. This issue is becoming increasingly relevant as climate change continues to influence weather patterns and environmental conditions, potentially affecting public health outcomes, particularly respiratory health. Method: The research method used is descriptive observational with an ecological study approach according to time which aims to see climate variability with ARI cases. Analyses were conducted to test the correlation between ARI cases and various climatic parameters, so as to obtain a comprehensive understanding of climatic factors that can affect the incidence of ARI. Results: The results of univariate analysis showed that during the period 2015 - 2023 the average ARI cases amounted to 9,815 cases / month, the average temperature was 28.31˚C, the average humidity was 73.49%, the average rainfall was 12.52 mm / month, the average length of sunshine was 7.42 hours, and the average wind speed was 2.55 km / hour. The correlation test results show that, maximum temperature (p = 0.002), average temperature (p = 0.003), average humidity (p = 0.008), wind direction with maximum speed (p = 0.000) have a significant relationship with ARI cases in Semarang City. While the average rainfall parameter (p = 0.681) and the length of sunshine parameter (p = 0.752) have no relationship with ARI cases in Semarang City in 2015 – 2023. Conclusion: Maximum temperature parameter, average temperature parameter, average humidity parameter, and wind direction parameter at maximum speed have a significant relationship with ARI cases. Promotive and preventive efforts need to be made to reduce the risk of ARI transmission, especially at the turn of the season and the density of activities carried out in the community.